Policy reform in developing countries - Balassa, Bela A. (Oxford ; New York : Pergamon Press, 1977)
This volume addresses itself to questions of policy reform in developing countries. It brings together essays the author wrote between March 1974 and October 1976. The essays represent applications of the general principles of policy reform that are contained in the contribution introducing the volume.
Includes bibliographical references and index.
ne 07/06/2018
Loans
Keywords: Tariff; Economic policy; Underdeveloped areas; Developing countries